Halal Entrepreneurship by Using the Global Gotong-Royong (G2R) Tetrapreneur Approach: a Bibliometric Review and Research Framework - Rozaq Muhammad Yasin; P.L. Rika Fatimah; Diana Shofa (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to examine publication patterns on halal entrepreneurship by using the global gotong-royong (G2R) tetrapreneur approach. This study conducted a quantitative bibliometric analysis using the Scopus database from 2004 to 2025. The search terms